Degradasi Etika Murid Generasi Z (Kajian Kitab Maraqil ‘Ubudiyah Syarah Bidayatul Hidayah Bab Al-Qoul Fi Adab As-Suhbah Wa Al-Mu’Asyarah Ma’a Al-Khaliq Azza Wa Jalla Wa Ma’a Al-Khalq) - Auliya Sholikhatun; Robingun Suyud El Syam; Bambang Sugiyanto (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to: (1) Identify the ethical behavior of Generation Z; (2) Understand the ethical degradation of Generation Z students based on the Book Maraqil ‘Ubudiyah, commentary on Bidayatul Hidayah, particularly the chapter Al-Qaul fi Adab As-Suhbah wa Al-Mu’asyarah Ma’a Al-Khaliq Azza wa Jalla wa Ma’a Al-Khalq. This research employs a qualitative approach with a library research design. Data were collected through documentation studies, using primary sources such as the Book Maraqil ‘Ubudiyah, and secondary sources including the Qur’an, classical Islamic texts, scientific journals, previous theses, articles, and other relevant documents. The data were analyzed using content analysis techniques. The findings reveal that: (1) Ethical behavior among Generation Z has shifted significantly compared to previous generations. This generation tends to perceive ethics as a form of respect for individual freedom, yet often neglects norms of politeness, respect for authority, and social responsibility. Their ethical framework is largely influenced by cultural globalization, digital technology development, and the shifting values in family and education. Although values such as tolerance, equality, and openness are still upheld, there is a noticeable decline in etiquette within social interactions, such as diminished respect for teachers, parents, and peers. (2) Based on the analysis of Maraqil ‘Ubudiyah, it is evident that there is a significant ethical degradation among Generation Z students. The book emphasizes the importance of manners toward Allah, the self, and fellow human beings, including sincerity in actions, maintaining personal dignity, humility, modesty, and polite social conduct. However, in reality, many Generation Z students are abandoning these principles, as reflected in their individualistic behavior, lack of respect for teachers, weak sense of social responsibility, and the declining spirit of brotherhood (ukhuwah) in social interactions. This degradation is primarily influenced by the pervasive impact of social media, educational models that prioritize cognitive aspects over character development, and the weak internalization of ethical values as taught in the aforementioned book.